Pediatric Drug Labeling and Imperfect Information - Wilfond, Benjamin S. (The Hastings Center report, 2020)
I first became aware of bioethics in the spring of 1980. I had spent a thirty-six-hour shift shadowing a medical resident, and I was struck that many of the resident's decisions had ethical dimensions. The next day, I came across the Hastings Center Report, and I realized I wanted to explore ethical issues I found implicit in clinical care, even though I still wanted to become a pediatrician. In September 2019, when I attended my first meeting of the U.S. Food and Drug Administration's Pediatric Advisory Committee, as a pediatric pulmonologist, I had the same sense of awe and curiosity that I had forty years ago. What had appeared initially as somewhat technical decisions about the regulation of drug labeling was suffused with ethical questions. The committee was asked to discuss possible changes to the labeling of two previously approved drugs.